(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This research aims to introduce the importance of electronic marketing and the extent of its impact on the quality of the insurance service in general, and the national insurance company in particular, and the advantages it can achieve, an increase in its competitiveness, as well as contributing to increasing the efficiency of the performance of the insurance company. The research relied on the questionnaire form as a main tool for obtaining data and information by the 70 questionnaire questionnaires required for the field side of the research, as they were distributed and retrieved in full, and all of them are suitable for analysis. The sample .The questionnaire was designed with three axes, the first was devoted to the identification information for the interviewees, while the second included electronic marketing and the third included the quality of insurance service. After examining the reality of the marketing activity in the National Insurance Company, the researcher reached a set of recommendations that emphasize the importance of electronic marketing to keep pace with global insurance companies, and take advantage of these advantages in the field of work of the National Insurance Company. The impact is also evident through the change in the quality of the insurance service in order to reach the largest segment of the target customers through electronic marketing and to know the appropriateness of the services provided by the company and to reach the largest number of potential customers and to retain the existing customers.